Cracow print of 1652 dedicated to the abbess of the convent in Zwierzyniec – Eufrozyna Korycińska - Muraszko, Michał Stanisław (Folia Toruniensia, 2017)
The communication presents the Cracow printing of the work by Bernard of Clairvaux The manner to live a wise and good life, which was published in the publishing house of the widow and successors of Franciszek Cezary in 1652. The copy discussed here was found during inventory works in the Archdiocesan Archive in Gniezno. It turns out that Polish bibliographies and printed catalogues fail to include this publication. The edition was dedicated to the abbess of the convent in Zwierzyniec – Eufrozyna Korycińska by Michał Melecius. It consists of pages from the earlier publication of the work in 1630.